Ursolic Acid Limits Salt-Induced Oxidative Damage by Interfering With Nitric Oxide Production and Oxidative Defense Machinery in Rice - Long, Meijuan; Shou, Jianyao; Wang, Jian; Hu, Weizhen; Hannan, Fakhir; Mwamba, Theodore M.; Farooq, Muhammad A.; Zhou, Weijun; Islam, Faisal (Frontiers in Plant Science, 2020)
Crops are frequently encountered with abiotic stresses, and salinity is a prime factor that suppresses plant growth and crop productivity, globally. Ursolic acid (UA) is a potential signaling molecule that alters physiology, biochemical processes and activates defense mechanism in numerous animal models; however, effects of UA in plants under stress conditions and underlying mechanism of stress alleviation have not been explored yet. This study examined the effects of foliar application of UA (100 μM) to mitigate salt stress in three rice cultivars (HZ, 712 and HAY). A pot experiment was conducted in a climate-controlled greenhouse with different salt stress treatments. The results indicated that exposure of NaCl induced salinity reduces growth of rice cultivars by damaging chlorophyll pigment and chloroplast, particularly at higher stress level. Application of UA alleviated adverse effects of salinity by suppressing oxidative stress (H2O2, O2-) and stimulating activities of enzymatic and non-enzymatic antioxidants (APX, CAT, POD, GR, GSH, AsA, proline, glycinebutane), as well as protecting cell membrane integrity (MDA, LOX, EL). Furthermore, UA application brought about a significant increase in the concentration of leaf nitric oxide (NO) by modulating the expression of NR and NOS enzymes. It seems that UA application also influenced Na+ efflux and maintained lower cytosolic Na+/ K+ ratio via concomitant up-regulation of OsSOS1 and OsHKT1;5 in rice cultivars. The results of pharmacological tests have shown that supply of NO scavenger (PTI) completely reversed the UA induced salt tolerance in rice cultivars by quenching endogenous NO and triggering oxidative stress, Na+ uptake and lipid peroxidation. The PTI application with UA and sodium nitoprusside (SNP) also caused growth retardation and a significant increase in Na+ uptake and oxidative stress in rice cultivars. This suggests that UA promoted salt tolerance of rice cultivars by triggering NO production, limiting toxic ion and reactive oxygen species (ROS) accumulation. These results revealed that both UA and NO are together required to develop a salt tolerance response in the rice.